The prevalence and clinical impact of trauma exposure and post-traumatic stress disorder in a psychiatric population in Iceland - Anna Margrét Hrólfsdóttir 1992- (2019)
A growing body of research has demonstrated a high prevalence of traumatic life experiences and post-traumatic stress disorder (PTSD) among individuals with mental illness, compared to the general population. However, traumatic events are often overlooked in the mental health system, and PTSD underdiagnosed or misdiagnosed. As a result, trauma-related symptoms are left untreated in a large majority of mental health consumers. This may result in poor engagement in treatment, impeding recovery from comorbid psychiatric disorders, and leading to an increased healthcare burden. The aim of the present study was to examine the prevalence of lifetime traumatic events, particularly adverse childhood experiences, and PTSD in a diagnostically diverse sample of psychiatric patients seeking mental health services in Iceland. Moreover, the purpose was to examine whether PTSD is being underdiagnosed by mental health professionals and to assess the psychiatric comorbidity with PTSD. Lastly, we examined the association between PTSD and mental health care utilization. Participants were 167 adults (113 women and 54 men), aged 18-69 years, currently seeking mental health services at the psychiatric ward of Landspítali, The National University Hospital of Iceland, between the 12th of April 2018 and 19th of March 2019. Results indicate that 97% of participants had experienced at least one traumatic event in their lifetime (M = 7.15). Interpersonal violence, such as sexual and physical assaults were the most common types of events experienced. Adverse childhood experience was reported by 95% of participants (M = 4.6). Emotional neglect and living with household members who were mentally ill or suicidal were the most frequent types of adversities reported during childhood. The average score on the PCL-5 was 35.9 in this sample, and 83 (55%) of the sample met criteria for PTSD based on the PCL-5 (cut-off score ≥33). Only 2.7% (4/144) of individuals who met PTSD criteria (PCL-5 ≥33) in the study had a registered diagnosis of PTSD in the ...